A Comprehensive Study of Various Challenges and Constraints in Wireless Sensor Networks (WSNs) - Panda, Sucheta; Bibhuprada B. Priyadarshini, Sushree (International Journal of Computer Sciences and Engineering, 2026)
Numerous applications are possible for Wireless Sensor Networks (WSNs). However, there are a number of implementations where the sensor data is useless and may lead to an false analysis of the provided information, especially if the coordinates information is unknown. Because of this, localization is crucial to many WSN operations. The problems and difficulties preventing the position of the sensor nodes in WSNs are thoroughly examined in this research. The fundamental concept behind a sensor network is to disperse tiny sensing devices which is capable of detecting changes in incidents or parameters and interacting with other devices over a defined geographic area for a variety of objectives, such as target tracking, vigilance, and environmental tracking. It is profitable to be utilized in great abundance in the future by integrating sensor technologies with computing power and wireless connectivity. A variety of security risks are also brought on by the use of wireless communication technology. In this essay, issues and difficulties with wireless sensor networks are surveyed.